2016
DOI: 10.3389/fnmol.2016.00099
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Regulation of the Adenosine Kinase Gene during Early Postnatal Brain Development and Maturation

Abstract: The ubiquitous metabolic intermediary and nucleoside adenosine is a “master regulator” in all living systems. Under baseline conditions adenosine kinase (ADK) is the primary enzyme for the metabolic clearance of adenosine. By regulating the availability of adenosine, ADK is a critical upstream regulator of complex homeostatic and metabolic networks. Not surprisingly, ADK dysfunction is involved in several pathologies, including diabetes, epilepsy, and cancer. ADK protein exists in the two isoforms nuclear ADK-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 46 publications
3
30
0
Order By: Relevance
“…Interestingly, strong neuronal expression of ADK has been detected in human fetal brains (gestational week 13; temporal cortex) [26]. Dynamic changes in ADK gene transcription during early postnatal brain development was also documented, and binding of transcription factor specificity protein 1 to the ADK promoter influences the regulation of ADK expression [27].…”
Section: Overexpression Of Adk In Rementioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, strong neuronal expression of ADK has been detected in human fetal brains (gestational week 13; temporal cortex) [26]. Dynamic changes in ADK gene transcription during early postnatal brain development was also documented, and binding of transcription factor specificity protein 1 to the ADK promoter influences the regulation of ADK expression [27].…”
Section: Overexpression Of Adk In Rementioning
confidence: 99%
“…Potential gene regulatory mechanisms including DNA promoter methylation, histone modifications and transcription factor binding may influence the dynamic regulation of the ADK gene during early postnatal brain development and maturation. Recent study indicated that binding of transcription factor specificity protein 1 to the ADK promoter influences the regulation of ADK expression [27].…”
Section: Review Adenosine Kinase a Common Pathologic Biomarker For Hmentioning
confidence: 99%
See 1 more Smart Citation
“…ADK has two isoforms: a long isoform, ADK-L, dominantly located in the nucleus [15]; and a short isoform, ADK-S, located in the cytoplasm [16]. The expression of ADK-L and ADK-S is dynamic during development with differentiated patterning; for example, ADK-L is dominantly expressed in early postnatal brain development, but then an ADK-S expression pattern becomes dominant in adult brain tissue [17]. This differential expression suggests a distinctive role for ADK-L (versus ADK-S) on proliferation and differentiation -two major nuclear activities that are tightly linked to cancer pathology [18].…”
Section: Introductionmentioning
confidence: 99%
“…This discrepancy may be explained by our antibody, which was selected for its optimal labeling in temporal lobe fixed‐tissue samples but has preferential recognition of the long isoform of ADK. ADK isoforms are developmentally regulated in the brain; the short isoform of ADK preferentially locates to the cytoplasm for adenosine clearance, whereas the long isoform is nuclear, with mainly epigenetic regulatory roles 35 …”
Section: Discussionmentioning
confidence: 99%